DIAGNOSA PENYEBARAN HAMA DAN PENYAKIT PADA KELAPA SAWIT MENGGUNAKAN SISTEM PAKAR - Budiarti, Rike Limia; Kahar, Novhirtamely; Utari, Arsyna Retno (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2019)
Bayes method can be used to build intelligent systems, in this study Bayes method was built by using an expert system to diagnose diseases and pests on oil palm plants, an expert system that was built web-based using PHP and MySql programming languages. This application can help the oil palm farmers in consulting about diseases and pests of oil palm plants based on the knowledge of the experts implemented in the application.